A Study of Research Papers on Punjabi stemming with special reference to Brute Force approach - Singh, Harjit (International Journal of Computer Sciences and Engineering, 2019)
For processing a natural language, the individual words of the text need to be processed. But the suffixes and prefixes attached to the words arises ambiguity problems and make the process more difficult. Stemming is the process of removing any suffixes or prefixes from the word to get the root word. Global languages like English took the advantage that much research has been done for stemming. Punjabi is an Asian language used by people of India‟s Punjab state and Pakistani Punjab state. Shahmukhi script is used in Pakistan and Gurumukhi script is used in India to write Punjabi. Although there are limited resources available for this language, yet some efforts have been made to develop stemmers for Punjabi language. This paper puts a light on those research papers which are published on Punjabi stemming with a special reference to Brute Force approach since it is used in almost all the research papers discussed here.